Y=ln(x-1)+ln(11-x)

Simple and best practice solution for Y=ln(x-1)+ln(11-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=ln(x-1)+ln(11-x) equation:


Simplifying
Y = ln(x + -1) + ln(11 + -1x)

Reorder the terms:
Y = ln(-1 + x) + ln(11 + -1x)
Y = (-1 * ln + x * ln) + ln(11 + -1x)
Y = (-1ln + lnx) + ln(11 + -1x)
Y = -1ln + lnx + (11 * ln + -1x * ln)
Y = -1ln + lnx + (11ln + -1lnx)

Reorder the terms:
Y = -1ln + 11ln + lnx + -1lnx

Combine like terms: -1ln + 11ln = 10ln
Y = 10ln + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
Y = 10ln + 0
Y = 10ln

Solving
Y = 10ln

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = 10ln

See similar equations:

| sinx=x^2/625pi^2 | | (6+z)(5z+1)=0 | | 21+3y-7=11y-10-2y | | A=b•h/2 | | 6(x-1/3)=2(x+23) | | 3=60-x | | -4(n+3)=-3n-2 | | 21-x=8 | | 3(4-8)=1/5(35x+30) | | -7(6+8r)-3r=17 | | 2y+x+-2x+3x=180 | | (1-x)+x=1.008 | | ln(7x-4)=lm(2x+11) | | 3x^3+7x^2+4x= | | 0.2(p+4)-0.7(p+2)=-3 | | 27x+21= | | (5x^2-30)/150x=1/6 | | a=22/7x45/2² | | 10-8(3-s)+5(s+3)=30 | | 30x^2-38x+12=0 | | 22/7(45/2)² | | X+3=(X-1)*2 | | 7y-25=-33+6y | | 20x^2-11-4= | | 4n^2-39+95=0 | | 5y-14=-22+y | | 3(q-3)+4q-1=5q+5+2q | | X^2+2ax=b | | -51=7(-1+6p)-6(7+7p) | | 3m+7+3(3m-4)-4(m+4)=0 | | 100=1/2*5t^2 | | 100=1/2(5)t^2 |

Equations solver categories